Treatment in the context of confinement - Ann-Karina Henriksen; Kajsa Nolbeck; Sofia Enell; Maria A. Vogel; Peter Andersson (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract In this article the authors present a meta-synthesis of their studies on secure institutions in Sweden and Denmark. The aim of the metasynthesis is to explore how the context of confinement shapes the possibilities for providing treatment and positive change for at-risk youth. Drawing on meta-synthesis methodology the authors extract content from nine studies published in 20 articles. We highlight three dimensions, which are a) treatment practices and behavioural regulation, b) the carceral materialities and sociomaterial practices, and c) relations. We argue that while treatment is curtailed by confinement, improvements can be made to support more successful change among at-risk youth and smooth their transition into adulthood.